2017
DOI: 10.55612/s-5002-033-007
|View full text |Cite
|
Sign up to set email alerts
|

A review of ten years of implementation and research in aligning learning design with learning analytics at the Open University UK

Abstract: There is an increased recognition that learning design drives both student learning experience and quality enhancements of teaching and learning. The Open University UK (OU) has been one of few institutions that have explicitly and systematically captured the designs for learning at a large scale. By applying advanced analytical techniques on large and fine-grained datasets, the OU has been unpacking the complexity of instructional practices, as well as providing conceptual and empirical evidence of how learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 46 publications
2
11
0
2
Order By: Relevance
“…Moreover, the analysis was complemented by data from a survey measuring student satisfaction, learning performance data, academic retention, and institutional analytics data, such as course level, discipline, class size. Rienties et al (2017) reviewed 10 years of work on aligning learning design with learning analytics at the Open University UK, and found that in some of their studies revealed that "learning design decisions made by OU teachers seem to have a direct and indirect impact on how students are working online and offline, which in part also influenced their satisfaction and learning outcomes"(p. 147) and that "how teachers mix learning design activities substantially impacts what students do on a weekly basis, whereby between 40-69% of variance of VLE engagement is predicted by learning design and its module characteristics" (p. 147).…”
Section: Learning Design In Learning Management Systemsmentioning
confidence: 99%
“…Moreover, the analysis was complemented by data from a survey measuring student satisfaction, learning performance data, academic retention, and institutional analytics data, such as course level, discipline, class size. Rienties et al (2017) reviewed 10 years of work on aligning learning design with learning analytics at the Open University UK, and found that in some of their studies revealed that "learning design decisions made by OU teachers seem to have a direct and indirect impact on how students are working online and offline, which in part also influenced their satisfaction and learning outcomes"(p. 147) and that "how teachers mix learning design activities substantially impacts what students do on a weekly basis, whereby between 40-69% of variance of VLE engagement is predicted by learning design and its module characteristics" (p. 147).…”
Section: Learning Design In Learning Management Systemsmentioning
confidence: 99%
“…For example, data extracted, visualized, and analysed by educational researchers and practitioners through LMS dashboards can help them design interventions and personalized learning opportunities (Blumenstein, 2020; Larusson & White, 2014). Learning design refers to an instructional plan that facilitates making pedagogically‐informed decisions about activities and resources optimizing learning in a learning environment (Blumenstein, 2020; Gašević et al, 2016; Mangaroska & Giannakos, 2019; Rienties et al, 2017). Essentially, learning design considers context, analytics, practice, and pedagogical theories to address challenges in improving educational processes (Mangaroska & Giannakos, 2019; Mor & Craft, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Once a suitable theoretical approach is identified, the next step is constructing a learning design that translates theory and pedagogic strategies into practice. Previous research showed that the learning design elements (e.g., resources, types of learning activities, and assessment tools) could directly affect the quality, quantity, and usability of data on student learning (Gašević et al, 2015; Lockyer et al, 2013; Rienties et al, 2017). Also, the learning design plays a significant role in the interpretability of the LMS data in relation to student performance (Rogers et al, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…LA analytics allows teachers to provide feedback to students on what students do and the progress they make. Rienties et al (2017) state that while there has been claims that learning design impacts on the effectiveness of learning and teaching, LA provides the opportunity to provide evidence of such impact. LA at the OU is based on an institutionally approved learning design taxonomy consisting of a number of learning design activities namely (1) assimilative; (2) finding and handling information; (3) communication; (4) productive;…”
Section: La As Informing Learning Design and Pedagogymentioning
confidence: 99%